Colonization of arbuscular mycorrhizal fungi (AMF) in the rhizosphere of robusta coffee plant (Coffea canephora) - Farha Aulia; Fatimah Istiqomah Nur; Ade Muliasari Astri; Hidayati Rohmah Fatchur; Lili Dahliani; Merry Meliala Gloria; Aidil Azhar (E3S Web of Conferences)
In this study arbuscular mycorrhizal fungi (AMF) colonization in the soil at the Bangelan Robusta coffee plantation, Malang, East Java was observed in two different locations with different plant ages, 49 and 10-year-old. The soil and root samples were collected from 0-50 cm and >100 cm from the plant base to observe the variation in the genus of AMF, the number of spores in the soil, and AMF infection in the roots of robusta coffee. A wet screening method was applied to observe the AMF spores in the soil. 250 µm, 125 µm, and 63 µm sieve meshes were used to collect the AMF spores from the 10 g soil sample. Root infection was observed using Philips and Hayman’s staining roots method. The results show that AMF has a root infection in the coffee roots of both 49-year-old and 10-year-old coffee plants. A higher spore number trend in the soil was found in the coffee farm with 49-year-old coffee plants than in the soil with 10year-old coffee plants. Higher root infection was found in the roots collected from 0-50 cm from the plant-based. Morphologically, the AMF genera found in the robusta coffee plantation were Glomus and Acaulospora, while the Acaulospora spore number was found to be higher than Glomus. The AMF infection rate in the robusta coffee roots was relatively low, ranging from 20% to 30%.